Media Relations Activities of Syariah Hotel Solo in Improving Corporate Image - Fikri Rahman; Mohammad Luthfi (Universitas Darussalam Gontor, 2018)
AbstractMedia relations are the attempt to achieve a maximum publication or broadcasting in order to create people awareness. The success of public relations to build image can be obtained from the harmonious relations with the media relations. Syariah Hotel Solo presents a new brand identity which is easily recognized by its preferences to use the ornamental pattern which is rooted in Islamic tradition, but was able to compete in news coverage in the media. This research aims to know media relations activities and the challenges conducted by Syariah Hotel Solo in order to improve the company’s image. The method used is descriptive qualitative. Techniques of data collection are through interviews, observation and documentation. The results of research show that media relations activities performed by Syariah Hotel Solo in order to improve corporate image are: Press Conference, Press Briefing, Press Tour, Press Release, Press Luncheon, Press Interview, Media Visit, and Greeting Media Partner’s Anniversary. Some of the activities are implemented formally and informal. The obstacles are adjusting the date of internal hotel activities with media’s schedule and competition with other hotel’s news. This research is expected to become consideration for public relations of Syariah Hotel Solo in implementing media relation activities. Keyword: Media Relations, Public Relations, Syariah Hotel Solo